2013
DOI: 10.1063/1.4804639
|View full text |Cite
|
Sign up to set email alerts
|

Tube transport of water vapor with condensation and desorption

Abstract: Attenuation and delay of active tracers in tube transport is an important current problem, but its full explanation is still lacking. To this end a model is introduced, where part of a tracer undergoes condensation and evaporation, treated as a diffusion-type process, in addition to Taylor dispersion. Condensation of water was verified by high-speed imaging, and the model solution fitted the breakthrough curves of laboratory measurements with pulses of water vapor of varying relative humidity. The model provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The nal delay was calculated by Eq. 1 and is highlighted in the development of humidity, but also to the wall material (Bloom et al, 1980), its age, and to the presence of aerosols (Mammarella et al, 2009;Nordbo et al, 2013). Humidity also has an eect on the lag of the measured χ CO 2 , although in an attenuated form, due to solubility in water.…”
Section: Raw Data Processing Diagnosticsmentioning
confidence: 99%
“…The nal delay was calculated by Eq. 1 and is highlighted in the development of humidity, but also to the wall material (Bloom et al, 1980), its age, and to the presence of aerosols (Mammarella et al, 2009;Nordbo et al, 2013). Humidity also has an eect on the lag of the measured χ CO 2 , although in an attenuated form, due to solubility in water.…”
Section: Raw Data Processing Diagnosticsmentioning
confidence: 99%
“…To date a comprehensive explanation for the amplitude and phase shifts is missing. However, Nordbo et al (2013) showed promising development in this respect.…”
Section: Using External H 2 O In Correcting Ch 4 Fluxesmentioning
confidence: 99%
“…Adsorption/desorption of H 2 O molecules on the sampling tube walls and filters (closed-path gas analysers only) cause amplitude and phase shifts compared to an unperturbed, ideal signal (Fratini et al, 2012;Ibrom et al, 2007a;Mammarella et al, 2009;Massman and Ibrom, 2008;Nordbo et al, 2013;Runkle et al, 2012). Thus, H 2 O lag times tend to be longer than for other gases in the same sampling tube and attenuations of H 2 O fluctuations are enhanced.…”
Section: Using External H 2 O In Correcting Ch 4 Fluxesmentioning
confidence: 99%
“…This is due to adsorption and desorption of H 2 O to sampling tube walls, a process which cannot be described accurately with Eq. (3) (Nordbo et al, 2013). Hence different transfer functions have been proposed for H 2 O (De Ligne et al, 2010;Nordbo et al, 2014).…”
Section: Co 2 and H 2 O Fluxes Corrected With The Four Methodsmentioning
confidence: 99%